A Case of Central Nervous System Post-Transplant Lymphoproliferative Disorder Following Haploidentical Stem Cell Transplantation in a Patient With Acute Lymphoblastic Leukemia. (August 2022) - Zhu, Haibo; Li, Qing; Liu, Yunyang; Feng, Xuequan; Deng, Qi
We present a differential diagnosis of an intracranial lesion following haploidentical stem cell transplantation (haplo-SCT) in a female patient with acute lymphoblastic leukemia (ALL). This patient received an anti-CD19-chimeric antigen receptor (CAR) T-cell therapy for refractory B-cell ALL and obtained minimal residual disease (MRD)-positive (0.03%) complete remission (CR). Then the patient received a bridging therapy of haplo-SCT. After bridging therapy, the patient maintained MRD-negative and full donor chimerism in bone marrow (BM) and was negative for Epstein–Barr virus (EBV)-DNA copy in peripheral blood. At 91 days after haplo-SCT, the patient presented with dizziness and fatigue and magnetic resonance imaging (MRI) demonstrated an intracranial lesion. The diagnosis of isolated extramedullary relapse (IEMR) was temporarily considered. Then next-generation sequencing (NGS) identified positive EBV-DNA in the cerebrospinal fluid, although EBV-DNA in the peripheral blood was negative. Furthermore, the positive EBV-DNA by NGS and complete donor chimerism in the brain tissue confirmed the diagnosis of central nervous system post-transplant lymphoproliferative disorder (CNS-PTLD). However, the EBV-encoded small RNAs (EBERs) in situ hybridization was sparsely positive. The patient was subsequently treated with anti-CD22-CAR T cells in combination with Zanubrutinib, but the disease progressed quickly and died. Donor chimerism examination of focal biopsy provides important evidence for diagnosing PTLD. Furthermore, NGS detection of EBV-DNA in local lesions is more valuable for diagnosing PTLD than detection of EBV-DNA in the peripheral blood. Trial registration: The patient was enrolled in a clinical trial of ChiCTR1800019622 and ChiCTR1800019298 .